Indek Kepuasan Pasien Suatu Rumah Sakit Swasta di Purwokerto - Suroso, Jebul (Jurusan Keperawatan FIKES UNSOED, 2011)
Hospital as a health care facility seeks to create quality health care, affordable and increase patient satisfaction. This study aims to identify satisfaction (assessment) to community health services on the installation of inpatient, outpatient, radiology, pharmacy and laboratory at a private hospital in Noida covering 14 elements of the service. The study design was descriptive survey techniques involving 120 respondents consisted of patients and former patients of the hospital taken by proportional random sampling technique. Analysis using the method of service performance in order to obtain the results of the research community satisfaction index (HPI) for the installation service inpatient, outpatient, radiology, laboratory and pharmacy are B (Good). Discipline of officers and timeliness into aspects that have the highest scores in five areas of the hospital services. There IKM components with sufficient predicate, ie courtesy and hospitality registration officer. There are no components that are predicated A or very good. It is suggested that these findings into consideration manajmen hospitals in improving quality of care, especially in the process of acceptance or enrollment of patients.